Effects of the Tax Cuts and Jobs Act on State Individual Income Taxes - Erin Huffer; John Iselin; Frank Sammartino; David Weiner (Washington University Journal of Law & Policy, 2019)
This article considers how the changes in the federal tax code will affect states whose tax codes link to the federal tax code. The article first summarizes the different parts of the federal code state tax codes link to, most importantly by linking to the definition of income. The article then describes the provisions of the Tax Cuts and Jobs Act that will have the biggest effect on state taxes. The article then uses four sample states (Missouri, Colorado, Utah and New York) and the District of Columbia to analyze how the changes contained in the Tax Cut and Jobs Act will affect: 1) the revenue collected by these jurisdictions; and 2) the state tax incidence across different income groups.
Keywords: Tax; Tax law; Tax Cuts and Jobs Act; Federal tax code; State tax; SALT; State and local taxes; TCJA